Development of an ultrasound-guided radiofrequency ablation technique in the equine cadaveric distal limb: histological findings and potential for treating chronic lameness - Amari, Martina; Rabbogliatti, Vanessa; Ravasio, Giuliano; Auletta, Luigi; Brioschi, Federica Alessandra; Riccaboni, Pietro; Dell’Aere, Silvia; Roccabianca, Paola (Frontiers in Veterinary Science, 2024)
Introduction Radiofrequency (RF) relieves chronic pain in humans, but it is unexplored in horses affected by chronic lameness. This study aims to describe the technique and the histological effects of ultrasound (US)-guided radiofrequency ablation (RFA) of palmar digital nerves (PDNs) in horse’s fetlock and pastern, ex vivo. Methods After assessing the US anatomy of lateral and medial PDNs in fetlock and pastern in vivo (n = 10 horses; 20 forelimbs), US-guided RFA was performed on these sites in cadaveric forelimbs (n = 10) applying four different settings with increasing invasiveness (n = 40 total treatments): 60°C, 6 min (GROUP LOW); 70°C, 4 min (GROUP MEDIUM); 90°C, 2 min (GROUP HIGH); 80°C, 8 min (GROUP VERY HIGH). Needle-tip-to-nerve proximity was assessed with US and methylene blue, injected through the port of the RF needle. Nerves were collected for microscopical assessment. Results Transverse palmaro-lateral and palmaro-medial US images of fetlock and pastern detected PDNs consistently, close to the palmar digital artery. With in-plane US technique, RFA was performed at target in 31/40 cases, with significantly higher number of failures in fetlock (p = 0.008). PDNs histology identified thermal injury/coagulation with axonal degeneration and collagen homogenation. Nuclear smearing of arterial leyomyocytes was also observed. Nerve coagulation was significantly associated with treatment (p = 0.03) and needle-tip-to-nerve proximity (US distance: p = 0.009; blue distance: p = 0.04). Discussion The PDNs were easily visualized and reached with the RF needle by US in-plane-guided technique. RFA produced axonal thermal damage and intensity-related coagulation effectiveness. To ensure effective nerve coagulation, it is crucial that the needle is accurately positioned in close proximity to the target nerve. Based on the histopathological findings, HIGH and VERY HIGH RFA treatments might be worth of being tested in vivo in clinical studies aimed at treating chronic lameness of the distal forelimb in horses.